2007
DOI: 10.1002/arch.20221
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of hemocyte counts with different developmental parameters during the last larval instar of the tobacco hornworm, Manduca sexta

Abstract: We determined the changes in hemocyte titer and in the abundance of hemocyte types of the tobacco hornworm Manduca sexta during the fourth and fifth larval stadium and the beginning of the pupal stadium. As we analyzed the samples of individual insects at daily intervals, we were able to correlate phenotypical features, body weight, as well as total protein content and lysozyme activity in the hemolymph with the observations on hemocytes. In the course of the fifth larval stadium, the hemocyte titer decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 60 publications
2
35
0
Order By: Relevance
“…The values found in this study are within the range of those found in earlier studies on food-limited M. sexta (Kramer et al, 1978;Siegert, 1986Siegert, , 1987Siegert et al, 1993;Bedoyan et al, 1992;Ismail and Matsumura, 1992;MeyerFernandes et al, 2001;Beetz et al, 2008). Surprisingly, the caterpillars on the low-nutrition diet managed to maintain their mass, including their dry mass, despite the decline in lipid stores.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The values found in this study are within the range of those found in earlier studies on food-limited M. sexta (Kramer et al, 1978;Siegert, 1986Siegert, , 1987Siegert et al, 1993;Bedoyan et al, 1992;Ismail and Matsumura, 1992;MeyerFernandes et al, 2001;Beetz et al, 2008). Surprisingly, the caterpillars on the low-nutrition diet managed to maintain their mass, including their dry mass, despite the decline in lipid stores.…”
Section: Discussionsupporting
confidence: 87%
“…Because immune function in M. sexta changes with age (Eleftherianos et al, 2008;Beetz et al, 2008;Booth et al, 2015), we included a fourth group of caterpillars that were fed on the highnutrition diet for a single day. We wanted to exclude the possibility that the results from the food-limited animals could be explained by developmental delay.…”
Section: Food Limitationmentioning
confidence: 99%
“…Methods for extracting hemocytes from medically important insects and lepidopteran model insects have previously been reported 9,14 . Hemocyte extraction methods are adapted according to the insect species, the developmental stage of the insect and its morphological features.…”
Section: Discussionmentioning
confidence: 99%
“…Fat body was collected 1 day later (5th instar-day 2) and 3 days later (5th instar-day 4). Because immune function changes with age in M. sexta (Beetz et al, 2008;Booth et al, 2015), we also collected fat body from control 5th instar-day 4 caterpillars to test whether any observed changes in gene expression in 5th instar-day 4 caterpillars could be attributed to ageing.…”
Section: Test Of Skin Sensitivity During Wasp Emergencementioning
confidence: 99%